Strategi Pengembangan Kurikulum Berbasis RnD untuk Meningkatkan Kompetensi Abad 21 pada Siswa Sekolah Menengah - Gustiana, Nadya; Miranda, Charin; Annas, Firdaus (Yayasan Lembaga Studi Makwa, 2024)
Education in the 21st century demands changes in curriculum approaches to prepare students for increasingly complex global challenges. One way to achieve this is by developing a Research and Development (R&D)-based curriculum that enhances students' competencies in various aspects, such as critical thinking, collaboration, communication, and creativity. This study aims to identify R&D-based curriculum development strategies that can improve 21st-century competencies in secondary school students. Using a qualitative approach, this research gathers data from various literature studies, as well as interviews with educators and education experts to gain a deeper understanding of the implementation of R&D-based curricula at the secondary school level. The results show that R&D-based curriculum development that integrates technology, project-based learning approaches, and the development of 21st-century skills is highly effective in enhancing students' competencies. Additionally, collaboration between schools, teachers, and industry stakeholders is also an important factor in the development of this curriculum. This study provides recommendations for educators and policymakers in designing and implementing curricula that meet the needs of students in the 21st century.